2021
DOI: 10.33233/rbfex.v19i5.4239
|View full text |Cite
|
Sign up to set email alerts
|

Efeito agudo do Mat Pilates sobre a variabilidade da pressão arterial ambulatorial em mulheres após a menopausa

Abstract: Background: After menopause, women increase the risk of developing cardiovascular disease. Physical exercise is one of the treatments for reducing the incidence of these diseases, and the Pilates method consists of a complete conditioning program. Aims: To verify the responses of Ambulatory Blood Pressure Monitoring (ABPM) and Blood Pressure Variability after a single session of Mat Pilates in non-obese post menopause women. Methods: This is a randomized crossover study with 15 normotensive postmenopausal wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Mat Pilates has resistance exercise characteristics (with features similar to bodyweight and functional fitness training), using accessories to increase the exercise load, but without using the classic apparatus of the method [ 21 ]. While Pilates does not appear on the Fitness Trends list, related terms are found in the global Top 20, such as resistance training, bodyweight training, and functional fitness training [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mat Pilates has resistance exercise characteristics (with features similar to bodyweight and functional fitness training), using accessories to increase the exercise load, but without using the classic apparatus of the method [ 21 ]. While Pilates does not appear on the Fitness Trends list, related terms are found in the global Top 20, such as resistance training, bodyweight training, and functional fitness training [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A combined training session reduced ARV in aging adults with hypertension [17,19]. However, a Mat Pilates exercise session [16] and a power training session [18] did not reduce short-term BP variability in hypertensive individuals. In the present study, a BT session reduced 24-h and daytime ARV of diastolic BP.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of a single bout of exercise in reducing BP variability is controversial [16][17][18][19]. A reduction in shortterm BP variability following a single bout of combined exercise was found in older adults with hypertension [17,19]; however, the benefits were not confirmed after a Pilates exercise session [16] and a power training session [18] in hypertensive individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term BP variability has an important association with autonomic cardiovascular system, and higher BP fluctuations can be associated to impairments on autonomic nervous system that results in high BP levels (Nardin et al, 2019). Few studies have evaluated the acute effects of exercise on ambulatory BP variability (Caminiti et al, 2019;Batista et al, 2020;Matias et al, 2020), and no previous studies have compared BP variability between older men and women after a single bout of exercise. A previous study demonstrated reduction in 24 h and daytime systolic (~2 mmHg) and diastolic (~1 mmHg) BP variability after a single bout of combined aerobic and resistance exercise in postmenopausal women with hypertension (Matias et al, 2020).…”
Section: Discussionmentioning
confidence: 99%